Problematic Internet Use Was Associated With Psychological Problems Among University Students During COVID-19 Outbreak in China - Xie, Xinyan; Zhu, Kaiheng; Xue, Qi; Zhou, Yu; Liu, Qi; Wu, Hao; Wan, Zihao; Zhang, Jiajia; Meng, Heng; Zhu, Bing; Song, Ranran (Frontiers in Public Health, 2021)
Background: As the coronavirus disease 2019 (COVID-19) pandemic progressed globally, school closures and home quarantine may cause an increase in problematic Internet use among students in universities. Such a traumatic stress event may also contribute to the development of posttraumatic stress disorder (PTSD), depressive and anxiety symptoms. This study aimed to evaluate the prevalence of PTSD, depressive, and anxiety symptoms as well as the predictive role of problematic Internet use in the above-mentioned psychological problems in university students. Methods: A cross-sectional study was conducted through an online survey of 8879 students in China between April 20 and April 26, 2020. The presence of PTSD, depressive and anxiety symptoms and problematic Internet use were evaluated using PTSD Checklist for DSM-5, the Center for Epidemiologic Studies Depression 9-item scale, the generalized anxiety disorder 7-item scale, and the Young diagnostic questionnaire, respectively. Sociodemographic information and the knowledge, attitude, and practice (KAP) towards COVID-19 data were also collected. Results: A total of 4,834 (54.4%) participants were female, and 7,564 (85.2%) were undergraduate students. A total of 615 students (6.9%) reported PTSD symptoms; 5.2% (465) and 10.1% (896) reported moderate to severe depressive and anxiety symptoms, respectively. The problematic Internet use was significantly associated with higher risk of PTSD, depressive, and anxiety symptoms (odds ratio 2.662 [95% CI, 2.239–3.165], odds ratio 4.582 [95% CI, 3.753–5.611], odds ratio 3.251 [95% CI, 2.814–3.757], respectively; all P < .001). Lower attitude and practice scores also contributed to the risk of depressive, anxiety, and PTSD symptoms (P < .05). Conclusions: Psychological problems should be paid more attention, and problematic Internet use may be a predictor when screening high-risk students for psychological problems. Our results will aid in timely psychological screening, which is meaningful in the prevention and intervention of psychological problems.